SELF–ACTUALIZATION OF HUMAN’S NEEDS: THE PORTRAIT OF A WOMAN’S STRUGGLE AGAINST PATRIARCHY IN NH. DINI’S NOVEL BANDUNGAN STREET - Asianti, Dwi Anggara (Language Circle: Journal of Language and Literature, 2010)
Patriarchy places Mur, the main character in NH DiniÃ¢â‚¬â„¢ s novel entitled Ã¢â‚¬Å“Bandungan StreetÃ¢â‚¬Â, as the secondary citizen, since its orientation is men. This condition impedes her to reach MaslowÃ¢â‚¬â„¢s hierarchy of needs. The apathy and sadness come since those needs cannot be met. It prompted her to be powerless. Then, she uses the Ã¢â‚¬ËœWill to PowerÃ¢â‚¬Â proposed by Nietzsche as to control the undesired condition to empower herself. At last, she can achieve self-actualization, to be the best she can be, as the highest needÃ¢â‚¬â„¢s rank. It proves that women can even be the better species if they are also given the same opportunity. Ã‚Â  Key words: patriarchy, will to power, self-actualization.